Catálise orgânica: planejamento, síntese e aplicações em reações orgânicas estereosseletivas - Fulas, Marcia [UNIFESP] (2015)
This work deals with the development of new Organocatalysts using 1,8-diaminoanthracene as a platform for the first time, and their application to the nitro-Michael reaction. The chemical structures of these Organocatalysts are based on the functional groups thiourea, guanidine and tertiary amine attached to the platform. The mode of action chosen for the design the new organocatalysts involves bifunctional action and activation of substrates through the hydrogen bonding interactions. In this research were synthesized 33 compounds, 12 of which were used as organocatalysts and used in the nitro-Michael reaction between dimethyl malonate and trans-?-nitrostyrene. Through this study, the Michael adducts were obtained up to 86.4% ee. From the results obtained in the application of the synthesized organocatalysts in the nitro-Michael reaction, it was possible to propose an enantiodifferentiation model.